A Study on Occupational Stress among Police - Dr. Santosh Kumar; Krupamani (International Journal of Indian Psychȯlogy, 2022)
The current study reveals that occupational stress among police the study says that police person they have moderate occupational stress, there is no significant difference in occupational stress among male and female police.